Genetically predicted smoking and body mass index mediate the relationship between insomnia and myocardial infarction - Limei Deng; Yuan Gao; Dongmei Wan; Zheng Dong; Yuming Shao; Jing Gao; Wenji Zhai; Qian Xu (Frontiers in Cardiovascular Medicine)
ObjectiveThis study aimed to investigate the causal relationship between insomnia and the risk of myocardial infarction (MI) and explore potential mediators such as smoking initiation, alcohol consumption and body mass index (BMI) using mendelian randomization (MR) analysis.MethodsData from 1,207,228 individuals of European ancestry were obtained from the UK Biobank and 23andMe for insomnia-related genetic associations. Genetic instruments for MI, smoking initiation, alcohol consumption, and BMI were derived from large-scale genome-wide association studies. Univariate MR analysis mainly utilized the inverse variance weighting method, and multivariable MR analysis assessed the mediation effects of smoking initiation and BMI.ResultsThe univariate MR analysis revealed a 96% increased risk of MI in individuals with insomnia [odds ratio (OR) = 1.96; 95% CI: 1.67, 2.31]. Smoking initiation and BMI were identified as potential mediators. The multivariable MR analysis indicated smoking initiation accounted for 29% of the total effect (95% CI: 13%, 61%), while BMI accounted for 15% (95% CI: 7%, 27%), with a combined mediation proportion of 54% (95% CI: 31%, 91%).ConclusionsThe results of this MR analysis demonstrate that insomnia increases the risk of MI. Quitting smoking and losing weight may reduce this risk; however, there is still a portion of the impact of insomnia on MI that cannot be explained. Therefore, further investigation into other potentially modifiable intermediate factors is necessary.